2015
DOI: 10.1364/oe.23.019288
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of sharply autofocused ring Airy Gaussian vortex beams

Abstract: Controlling the focal length and the intensity of the optical focus in the media is an important task. Here we investigate the propagation properties of the sharply autofocused ring Airy Gaussian vortex beams numerically and some numerical experiments are performed. We introduce the distribution factor b into the initial beams, and discuss the influences for the beams. With controlling the factor b, the beams that tend to a ring Airy vortex beam with the smaller value, or a hollow Gaussian vortex beam with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…Such a method can also be implemented in the generation of circular Airy beams (CABs), i.e., radially symmetric Airy beams. Due to great efforts devoted in the study of abruptly autofocusing beams, the CABs are experimentally demonstrated in the optical regime 30, 31 . Based on the Fourier transform (FT) method described above, the usual generation system of the CABs consists of two components, one of which imprints the required phase pattern and the other performs a FT.…”
Section: Resultsmentioning
confidence: 99%
“…Such a method can also be implemented in the generation of circular Airy beams (CABs), i.e., radially symmetric Airy beams. Due to great efforts devoted in the study of abruptly autofocusing beams, the CABs are experimentally demonstrated in the optical regime 30, 31 . Based on the Fourier transform (FT) method described above, the usual generation system of the CABs consists of two components, one of which imprints the required phase pattern and the other performs a FT.…”
Section: Resultsmentioning
confidence: 99%
“…The high-power OAM beam can be used in many applications besides free space communications, such as high-resolution imaging and special material processing [47] . In particular, for the destruction of necrotic biological tissue in the field of biomedical treatment, high-power vortex beams (like the ring Airy–Gaussian beam) have great potential and advantages [48] . Additionally, the manipulation of micro-particles under the radiation of high-power OAM beams may show improved performance.…”
Section: Discussionmentioning
confidence: 99%
“…21(c). Recently, a circular Airy vortex beam has attracted interest due to its autofocusing property, 130,131 which is a hollow beam carrying OAM, as shown in Fig. 21(d).…”
Section: Optical Trapping With Airy-gaussian Beamsmentioning
confidence: 99%